2009
DOI: 10.1111/j.1365-2672.2009.04610.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological analysis of composts produced on South Carolina poultry farms

Abstract: Aims:  The purpose of this study was to determine whether the methods used in compost operations of small and medium‐sized poultry forms resulted in the production of an amendment free of foodborne pathogens. Methods and Results:  Nine compost heaps on five South Carolina poultry farms were surveyed at different stages of the composting process. Compost samples were analysed for coliforms and enriched for Escherichia coli O157:H7, Salmonella spp. and Listeria monocytogenes. The waste materials and composting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
1
31
0
1
Order By: Relevance
“…10 5 CFU/g in fecal samples collected from broiler chicken flocks [19]. L. monocytogenes is usually absent (negative) in chicken litter and poultry compost, and this pathogen therefore appears not to be a significant issue in chicken litter or chicken litter-based organic fertilizers [6,30]. There are also growing concerns about the presence of antibiotic-resistant pathogens in animal manures from both on-farm exposure and off-farm contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 5 CFU/g in fecal samples collected from broiler chicken flocks [19]. L. monocytogenes is usually absent (negative) in chicken litter and poultry compost, and this pathogen therefore appears not to be a significant issue in chicken litter or chicken litter-based organic fertilizers [6,30]. There are also growing concerns about the presence of antibiotic-resistant pathogens in animal manures from both on-farm exposure and off-farm contamination.…”
Section: Introductionmentioning
confidence: 99%
“…This review thus focuses on the microbiological safety of chicken litter or chicken litter-based organic fertilizers. 26% surface and 6.1% internal samples (1st composting phase); absent in all samples (2nd composting phase) [30] E. coli is present in chicken litter with the prevalence rate as high as 100%; however, E. coli O157:H7 was not detected in chicken litter samples [28,29] or poultry compost samples [29,30]. The population of E. coli in reused chicken litter can reach up to 9.7 × 10 4 CFU/g while the population for single use litter has been found to be 4.2 × 10 5 CFU/g [6].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to a challenge study, chicken litter was analyzed for background mesophiles and screened for Salmonella, as described previously (30). Ten grams of chicken litter was mixed with 90 ml of saline and plated onto TSA-R.…”
mentioning
confidence: 99%
“…Chicken litter samples were adjusted to desirable moisture contents (30,40, and 50%) with sterile tap water using a spray nozzle (sterilized with 70% ethanol and rinsed with sterile tap water). A mixture of 3 Salmonella serovars was inoculated into the samples (1:100, vol wt Ϫ1 ) with a sterile spray nozzle at a final concentration of ca.…”
mentioning
confidence: 99%
“…Lung et al showed that E. coli O157:H7 inoculated at a level of log 10 7.00 CFU g −1 was nondetectable after 72 h in composted manure (83). Research by Shepherd et al showed that compost heaps covered with finished compost maintained temperatures under the physical covering that were around 7 to 15.5°C higher than in an uncovered heap, resulting in a faster reduction of E. coli O157:H7 than was observed in heaps covered with fresh straw or left uncovered (84). This validated recommendations of the U.S. Environmental Protection Agency for covering fresh compost (84).…”
Section: Control In Animal Wastementioning
confidence: 99%